2020
DOI: 10.2147/ccid.s262803
|View full text |Cite
|
Sign up to set email alerts
|

<p>Frontal Fibrosing Alopecia. An Example of Disrupted Aryl Hydrocarbon Receptor-Mediated Immunological Homeostasis in the Skin?</p>

Abstract: Sun protection has been recommended by public health authorities to reduce the risk of keratinocyte and melanocyte tumors, yet some sun exposure is required for vitamin D synthesis. Frontal fibrosing alopecia (FFA) is a cicatricial alopecia that has been reported to have an association with facial photoprotection. The brief review proposes the hypothesis that FFA arises as a result of excessive facial photo-protection with a resultant disturbance in immunological homeostasis mediated via the aryl hydrocarbon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Given that IDO is the first rate-limiting and inflammatory-inducing enzyme in the KP [ 39 ], we explored the molecular mechanisms underlying stress-induced depression. Accordingly, we measured two IDO isoforms, IDO1and IDO2, KP and its metabolites in the serum and brain tissue of mice harvested at the end of behavioral experiments by q-PCR, ELISA and HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…Given that IDO is the first rate-limiting and inflammatory-inducing enzyme in the KP [ 39 ], we explored the molecular mechanisms underlying stress-induced depression. Accordingly, we measured two IDO isoforms, IDO1and IDO2, KP and its metabolites in the serum and brain tissue of mice harvested at the end of behavioral experiments by q-PCR, ELISA and HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…A new hypothesis proposes that FFA may arise as a result of excessive facial photo-protection, with a resultant disturbance in immunological homeostasis mediated via the aryl hydrocarbon receptor-kynurenine pathway axis (AhR/KP), leading to the collapse of immune privilege at the hair bulge [ 43 ]. Overexpression of the aryl hydrocarbon receptor (AhR) in the epidermis of FFA and LPP has been newly described in both unaffected and affected scalp [ 44 ].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…How to reverse the immune response in the early stage of EMT, or develop a corresponding targeting carrier for PPARγ, so that the PPARγ inhibitors can accumulate around the hair follicle, will become the future treatment direction or strategy to help us integrate the recent FFA pathobiological insights and translate them into specific therapeutic benefits. Commonly, it is reported that FFA is related to thyroid disease and some other autoimmune diseases, such as scalp discoid lupus erythematosus, vitiligo, lichen planus, lichen planus pigmentosa, and Sjögren’s syndrome ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that the light protection provided by many facial care products reduces the synthesis of the tryptophan light product 6-formylindolo [3,2-b] carbazole (FICZ), which is a potent endogenous ligand of AHR, from the photooxidation of the essential amino acid L-tryptophan. It shows proinflammatory effects at lower concentrations and anti-inflammatory effects at higher concentrations ( 51 ). However, there is no definitive evidence of a causal relationship between sunscreens or environmental factors and FFA.…”
Section: Environmental Factorsmentioning
confidence: 99%